Analisis Pengaruh Kualitas Produk dan Strategi Promosi Terhadap Keputusan Pembelian Produk Wardah di Beauty House - Reni Yesi; Murdan Sianturi (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2021)
This study aims to determine whether product quality and promotional strategies have an influence on purchasing decisions for wardah products at Beauty House. This study uses data collection methods, namely field research using statement data (questionnaires). The sample method used is the slovin method, totaling 66 respondents to consumers of Wardah Beauty House products. Data analysis using multiple linear analysis method, coefficient of determination analysis, t test, f test using SPSS version 20. The results showed that there was a positive and significant influence on purchasing decisions for wardah products at Beauty House. The results of multiple linear regression analysis obtained that the regression equation Y = 0.748 + 0.455X1 + 0.544X2 it shows the regression coefficient of the product quality variable (X1) is 0.748. This means that if the quality of the product increases by one unit, it will have an influence on purchasing decisions of 0.455. For the promotional strategy variable (X2) of 0.544. This means that if the promotional strategy has increased by one unit, it will have an influence on purchasing decisions of 0.544. From the results of the two coefficients, the independent variable that has the most dominant influence on the dependent variable is the promotional strategy variable (X2) with a value of 0.544. Based on the test results the coefficient of determination (R^2) = 53.2%. The results show that purchasing decisions are influenced by product quality and promotion strategies by 53.2% and the rest is influenced by other factors not examined. The results of the partial test (t test) show that the results of the value of product quality (X1) on purchasing decisions (Y) show t counted 3.766 > t table 1.998 then product quality has an influence on purchasing decisions. The results of testing the promotional strategy variable (X2) on purchasing decisions (Y) show t count 3.746 > t table 1.998, then the promotion strategy has no effect and is significant on purchasing decisions. The overall test results (f test), calculated f (35,744 > 3.14), then the product quality and promotion strategy together have a positive and significant influence on purchasing decisions